A case of fatal disseminated adenovirus and drug‐resistant Pneumocystis pneumonia in a patient who received chemotherapy for mantle cell lymphoma. Issue 4 (22nd April 2023) - Yu, Bo; Saravanan, Lakshmi; Tran, Dena H.; Davies, Alexander J.; Kaur, Harpreet; Naraynanan, Shivakumar; Verceles, Avelino C.; Kim, Hyeong J.
Abstract: Adenovirus (ADV) may cause severe complications in hematopoietic stem cell transplant recipients, but disseminated ADV infections in patients who received chemotherapy alone for hematological malignancies are poorly understood due to the rarity of cases. Concomitant infection with Pneumocystis (PCP) is extremely rare. Despite being diagnostically challenging, a more specific workup needs to be initiated with a low threshold in patients who are exposed to agents with the potential to suppress T cells. We report a fatal case of disseminated ADV and drug‐resistant PCP pneumonia in a patient with mantle cell lymphoma who had only received combination chemotherapy. A 75‐year‐old man who was diagnosed with mantle cell lymphoma 10 months prior was admitted for mild hypoxic respiratory failure. Bendamustine, Rituximab, Cytarabine regimen had resulted in complete remission of his lymphoma, with the last cycle of chemotherapy administered 3 months prior to admission. CT of the chest revealed ground‐glass opacities concerning pneumonia. Initial laboratory tests were remarkable for mild leukopenia. The respiratory viral panel was only positive for ADV. He did not respond to empiric antibiotics for community‐acquired pneumonia and Trimethoprim / Sulfamethoxazole given later for positive Beta D Glucan (BDG) suggestive of Pneumocystis pneumonia. Then, he developed hemorrhagic cystitis, followed by liver and renal function derangement that prompted checking serum ADV viral load by polymerase chain reaction (PCR). This test took 1 week to return, with a viral load of 50, 000 copies/mL suggesting disseminated ADV infection. Despite initiation of Cidofovir, multi‐organ failure continued to progress, and the follow‐up viral load had doubled on Day 2. The patient passed away the same day shortly after transition to comfort care. T cell suppression seems to be a risk factor for disseminated ADV disease. Clinicians may need to maintain a low threshold to send serum quantitative ADV PCR when symptoms are not improved by antimicrobial treatment for more conventional infections in patients who received agents that are known to suppress T cells, such as Bendamustine.